PEMANFAATAN MASALAH MATEMATIKA TERBUKA DALAM PEMBELAJARAN SEBAGAI STRATEGI DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS : SYSTEMATIC LITERATURE REVIEW - Junita, Ni Ketut; Pujawan, I Gusti Ngurah; Ariawan, I Putu Wisna (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
Students' critical thinking skills in mathematics learning remain relatively low due to the dominance of conventional teaching that focuses on procedures and single correct answers. This study aims to analyze the effectiveness of open-ended mathematical problems in improving students' critical thinking skills, describe their implementation, and identify factors influencing their success. The method employed is a Systematic Literature Review (SLR) examining 22 selected articles obtained through searches on Google Scholar, ERIC, and Semantic Scholar databases, supplemented by manual reference searching, from a total of 212 identified articles. The article selection process was carried out using the identification, screening, eligibility, and inclusion stages based on the PRISMA guidelines, applying predefined inclusion and exclusion criteria within the publication range of 2016–2026. The results indicate that the use of open-ended mathematical problems is effective in enhancing students' critical thinking skills, evidenced by improvements in analysis, evaluation, and decision-making abilities, with a high effect size of 1.44. Implementation is carried out through stages of problem presentation, strategy exploration, discussion, and student-centered reflection. The success of this approach is influenced by problem quality, teacher competence, student engagement, and a supportive learning environment. Therefore, open-ended mathematical problems can serve as an effective alternative learning strategy to develop students' critical thinking skills.